2017
DOI: 10.1002/anie.201700576
|View full text |Cite
|
Sign up to set email alerts
|

Divalent Thulium Triflate: A Structural and Spectroscopic Study

Abstract: The first molecular Tm luminescence measurements are reported along with rare magnetic, X and Q bands EPR studies. Access to simple and soluble molecular divalent lanthanide complexes is highly sought for small-molecule activation studies and organic transformations using single-electron transfer processes. However, owing to their low stability and propensity to disproportionate, these complexes are hard to synthetize and their electronic properties are therefore almost unexplored. Herein we present the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…Divalent ions of these three metals have now been reported, mainly as cyclopentadienyl derivatives, and the majority involving thulium [35c, 56b, 68] . A few notable recent examples include a divalent thulium complex [Tm( μ ‐OTf) 2 (dme) 2 ] n ( 18 ) on which the first molecular Tm II luminescent measurements were reported [68a] . The luminescent measurements in corroboration with extensive EPR studies were used to unambiguously define the nature of the electronic ground state [68a] .…”
Section: Lanthanoid Complexes With Unusual Lanthanoid Oxidation Statesmentioning
confidence: 98%
See 1 more Smart Citation
“…Divalent ions of these three metals have now been reported, mainly as cyclopentadienyl derivatives, and the majority involving thulium [35c, 56b, 68] . A few notable recent examples include a divalent thulium complex [Tm( μ ‐OTf) 2 (dme) 2 ] n ( 18 ) on which the first molecular Tm II luminescent measurements were reported [68a] . The luminescent measurements in corroboration with extensive EPR studies were used to unambiguously define the nature of the electronic ground state [68a] .…”
Section: Lanthanoid Complexes With Unusual Lanthanoid Oxidation Statesmentioning
confidence: 98%
“…A few notable recent examples include a divalent thulium complex [Tm( μ ‐OTf) 2 (dme) 2 ] n ( 18 ) on which the first molecular Tm II luminescent measurements were reported [68a] . The luminescent measurements in corroboration with extensive EPR studies were used to unambiguously define the nature of the electronic ground state [68a] . Soon after, Tm II in the crown ether complex [TmI 2 (18‐crown‐6)] ( 19 ) was found to display field induced slow relaxation of magnetization [35c] .…”
Section: Lanthanoid Complexes With Unusual Lanthanoid Oxidation Statesmentioning
confidence: 99%
“…They showed that TPSS was one of the best density functionals, and that less accurate results were obtained when more Hartree–Fock exchange was included in the functional. Furthermore, lanthanide and actinide chemical properties have been extensively explored using DFT; for example, using the PBE0 density functional, or B3PW91 for mechanistic studies . Nonetheless, there is a lack of comparison between experimental data and computed data using different types of density functionals, for example, double hybrid functionals.…”
Section: Introductionmentioning
confidence: 99%
“…[Cu(Psalen OMe )](SbF 6 ) exhibits a c value of about 0.00070(5) cm 3 mol À1 while [Cu(Psalen tBu )](SbF 6 ) has a c value of about 0.0001(1) cm 3 mol À1 .B oth values are low but positive which indicates at emperature independentp aramagnetic (TIP) [39] behavior albeit the c value is more than seven times higher in [Cu(Psalen OMe )](SbF 6 ) than in [Cu(Psalen tBu )](SbF 6 ).I n these cases, the purity of the sample was corrected for magnetic impurities, [40] and the nature of the sample containment was chosen according to previousr eports (see Supporting Information for details). [41] The observation of this TIP behavior over the large temperature range indicates that the triplet state is not populated-or to av ery smalle xtent-at room temperature and this is in favor of ar elative large gap (À2J) between the open-shell singlet andt he triplet states (above 1000 cm À1 ).…”
Section: Magnetic Studiesmentioning
confidence: 99%